(untitled) (Research, Society and Development, 2022)
Self-inflicted violence refers to acts of self-mutilation and suicide attempts in individuals with intense psychological distress. This study is based on the hypothesis that living in the COVID-19 pandemic, by triggering and/or aggravating psychological suffering/illness, predisposes to acts of self-inflicted violence. To test this hypothesis, 493 Compulsory Notification Forms referring to cases of self-inflicted violence in one of the ten health districts in the city of Curitiba were analyzed between the years 2018 to 2020. The data was analyzed based on the evaluation of the association between categorical variables, using the chi-square test or Fisher’s exact test (p<0.05) and the computer program Stata/SE v. 14.1 StataCorpLP, USA. The results point to a 51.58% drop in the rates of self-inflicted violence in the period of the COVID-19 pandemic, compared to the previous period (2018-2019). However, people with mental disorders and/or disabilities are at greater risk of repeating the act of self-inflicted violence (p=0.000). Those findings coincide with international studies that took place in the same period, and can be attributed to the coping strategies adopted or to the failure to fill in the Forms and they point to the need for Public Policies for the promotion and prevention of mental health.